The First Record of Female Maturation of the Short-finned Eel, Anguilla bicolor bicolor, in the Coastal Waters of Thailand - Prasert Tongnunui; Nuengruetai Yoknoi; Pimwipa Pechnoi; Hideaki Yamada; Koetsu Kon (Tropical Life Sciences Research, 2016)
The objective of the present study was to provide reproductive biological information on the gonadal development of the short-finned eel, Anguilla bicolor bicolor, which inhabits the coastal waters of Thailand. Short-finned eels were collected from three coastal areas of Trang Province, southern Thailand, from September 2011 to December 2013. The gonads of 151 specimens were subjected to a histological analysis. The histological observations found both immature and maturing females. Based on the advanced oocytes within an entire ovarian section, the ovaries of the studied specimens were classified into three maturity phases: 1) the immature phase was defined by ovaries that showed oogonia and primary growth oocytes, 2) the developing phase was defined by ovaries that contained early vitellogenic-stage oocytes with some oogonia present along with cortical alveolar oocytes and many adipocytes, and 3) the late vitellogenic phase refers to ovaries that contained nearly entirely late-vitellogenic oocytes. The density of oocytes in juxtaposition to an adipose matrix is considered to represent the degree of gonadal development. The results of this study may be applicable in further defining the general spawning area of A. bicolor bicolor in regions of the Indian Ocean. Objektif kajian ini adalah untuk memberikan informasi biologi pembiakan untuk perkembangan gonad belut short-finned, Anguilla bicolor bicolor, yang mendiami kawasan perairan pantai Thailand. Belut short-finned telah dikumpul daripada tiga kawasan pinggir laut di Provinsi Trang, di Selatan Thailand, dari September 2011 hingga Disember 2013. Gonad daripada 151 spesimen telah menjalani analisa histologi. Daripada pemerhatian histologi, betina pramatang dan matang dijumpai. Berpandukan oosit lanjut dalam keseluruhan bahagian ovari, ovari-ovari spesimen yang dikaji telah diklasifikasikan kepada tiga fasa matang: 1) fasa pramatang telah dikenal pasti dengan kehadiran ovari yang mengandungi oogonia dan oosit pertumbuhan primer, 2) fasa perkembangan telah dikenal pasti dengan kehadiran ovari yang mengandungi oosit peringkat vitellogenik awal bersama dengan oogonia dan oosit korteks alveolar dan adiposit yang banyak, dan 3) fasa vitellogenik lambat yang merujuk kepada ovari yang mempunyai hampir kebanyakannya oosit peringkat vitellogenik lambat. Kepadatan oosit yang berdampingan dengan matriks adipos dianggap mewakili darjah pembesaran gonad. Keputusan kajian ini boleh diaplikasi untuk takrif secara lanjut kawasan peneluran A. bicolor bicolor di kawasan Lautan Hindi.